Synthesis of Fluorinated exo‐Glycals through Modified Julia Olefination. Issue 10 (18th February 2013) - Habib, Samuel; Larnaud, Florent; Pfund, Emmanuel; Lequeux, Thierry; Fenet, Bernard; Goekjian, Peter G.; Gueyrard, David
Abstract: An efficient synthesis of fluorinated enol ethers derived from carbohydrates is reported. A modified Julia olefination reaction of functionalized lactones with fluorine‐substituted sulfones gives the corresponding monofluorinated tri‐ or tetrasubstituted exo ‐glycals. Abstract : An efficient synthesis of fluorinated enol ethers derived from carbohydrates is reported. A modified Julia olefination reaction of functionalized lactones with fluorine‐substituted sulfones gives the corresponding monofluorinated tri‐ or tetrasubstituted exo ‐glycals.